Revamping Indian Agriculture : A Comprehensive Reform Strategy (International Journal of Scientific Research in Science and Technology, 2024)
Indian agriculture, a cornerstone of the nation’s economy, is currently beset by a range of challenges that threaten its sustainability, productivity, and global competitiveness. This research paper proposes a comprehensive reform strategy aimed at revitalizing the sector. The study begins by identifying key issues such as fragmented landholdings, inadequate infrastructure, limited access to technology, and the impacts of climate change. It then outlines a holistic agricultural approach that integrates production, marketing, and consumption, advocating for improved access to credit, sustainable farming practices, and strengthened farmer organizations. The paper emphasizes the importance of developing robust value chains, particularly through public-private partnerships, and highlights the need for policy reforms to enhance farmers’ access to advanced technologies and global markets. Fertilizer subsidy reforms are proposed to align with sustainable agricultural practices, including the transition to direct benefit transfers. The study also underscores the necessity of inclusive growth and social security measures, such as comprehensive crop insurance schemes and assured procurement at minimum support prices (MSP), to stabilize farm incomes. To address the growing threat of climate change, the paper advocates for significant investments in climate-resilient agriculture and efficient water management practices. Finally, the role of digital platforms, particularly the National Agriculture Market (eNAM), in modernizing the sector is explored, emphasizing its potential to create a more transparent, integrated, and efficient agricultural market. The proposed reforms, if implemented effectively, have the potential to transform Indian agriculture into a more resilient, productive, and globally competitive sector, ensuring food security and economic prosperity for millions of farmers across the country.